Layer-interface properties in 3D printed concrete: Dual hierarchical structure and micromechanical characterization. (December 2020) - Geng, Zifan; She, Wei; Zuo, Wenqiang; Lyu, Kai; Pan, Hao; Zhang, Yunsheng; Miao, Changwen
Abstract: Extrusion-based 3D printing is the manufacturing technology which shapes the material layer by layer. This deposition mode results in a weak interface between layers, which seriously deteriorates the mechanical performance of printed objects. It is well-known that bonding strength of layer interface is fundamentally controlled by the deposition process (time interval, interfacial humidity, etc.) and properties of printing material. In this paper, XCT/SEM image processing was introduced to analyze interfacial pore structure at different scales, while nano-indentation was utilized for characterizing the interface micromechanical performance. The results indicated that layer interface generates a dual hierarchical structure, where deformation ability of rough layer surface contributes to the macro-interface and hydrates structure dominates the micro-interface. The influences of such factors including material rheological properties, deposition time interval and interfacial humidity can be integrated in this dual hierarchical structure. Finally, an empirical model was proposed to combine dual hierarchical structure with bonding strength of layer interface in 3D printed concrete.